Biomechanical anticoagulation by spherical platelets in extracorporeal systems - Rui Ji; Yongjian Li; Jiang Li; Haosheng Chen (Proceedings of the National Academy of Sciences, 2026)
Extracorporeal life support, such as hemodialysis, often face the risk of blood coagulation, where systemic anticoagulation with heparin is routinely administered. However, this strategy is contraindicated in patients at high risk of bleeding. Inspired by the observation that rolling motion of spherical platelets avoids their exposure to tangential forces, an anticoagulation strategy is proposed based on platelet spherification for extracorporeal systems. Experimental results prove that spherical platelets retain activation pathways and capacity compared to discoid platelets. Mechanical activation is driven by tangential rather than normal forces, and maintaining rolling instead of sliding effectively prevents tangential force-induced activation. Molecular dynamics simulations reveal that tangential force acting on sliding discoid platelets separates the integrin α IIb β 3 head from the lower leg region to unfold and activate the integrin, while the normal force acting on rolling spherical platelets induces headpiece rotation without triggering unfolding, which effectively reduces integrin α IIb β 3 activation. In in vitro hemodialysis experiments, platelet spherification effectively minimized coagulation, while avoiding bleeding complications.